Legal Analysis of the Cihujung River Environmental Pollution Case by PT How Are You Indonesia (PT. HAYI) (Case study: Indonesia Disctrict Court Decision Number 735/PDT.G LH/2018/PN.Jkt.Utr) - Halim, Chandra; Shecillia (Mahadi: Indonesia Journal of Law, 2024)
Environmental pollution, especially river water pollution, is a crucial issue that has far-reaching impacts on ecosystems and public health. This pollution is often caused by irresponsible industrial activities, as seen in the case between the Ministry of Environment and Forestry of the Republic of Indonesia and PT How Are You Indonesia. Through strict law enforcement and the application of the principle of absolute liability, it is hoped that a deterrent effect can be created for the perpetrators of pollution and encourage better protection of the environment. In a verdict that partially granted the lawsuit of the Ministry of Environment and Forestry of the Republic of Indonesia against PT How Are You Indonesia, the judge found the defendant guilty of water pollution based on the principle of absolute responsibility. The defendant is required to pay compensation of more than 12 billion rupiah and daily forced money of 10 million rupiah if it is late in implementing the decision. Corporate liability for environmental pollution is regulated in Law No. 32 of 2009, but several aspects of the verdict need further review, such as the relationship between strict liability and tort, the clarity of the purpose of compensation, and the importance of applying additional administrative sanctions. In addition, the Act is considered less effective in establishing a commitment to reduce and reverse environmental damage.